Wandering spleen: A rare entity and a diagnostic dilemma - Kaur, Ravinder; Dua, Ashish; Dalal, Ashwani (Indian Journal of Radiology and Imaging, 2020)
Wandering spleen refers to a spleen that is ectopic in its location contrary to a normal spleen which rests in the left hypochondrium. Although it is a rare clinical entity seen in children, it can also be rarely seen in females of reproductive age group. We present one such case of wandering spleen which was misdiagnosed earlier as a sub-hepatic collection.
Keywords: Rare disease; spleen; wandering